18F-FDG and 18F-NaF PET/CT Findings of a Multiple Myeloma Patient With Thyroid Cartilage Involvement. (November 2015) - Oral, Aylin; Yazici, Bulent; Ömür, Özgür; Comert, Melda; Saydam, Guray
Abstract : Abstract: Thyroid cartilage is a very rare extramedullary involvement location in multiple myeloma. We present both 18 F-NaF and 18 F-FDG PET/CT findings of a multiple myeloma patient with thyroid cartilage involvement. In this patient, increased FDG and more intensely increased NaF uptake were seen on thyroid cartilage. In addition, some bone lesions had more intense NaF than FDG uptake, and some were only NaF avid. Although 18 F-FDG PET/CT has an important role in plasma cell neoplasms, we considered that 18 F-NaF PET/CT is also very useful to detect small lytic lesions that might be overlooked on 18 F-FDG PET/CT.